2010
DOI: 10.1002/ana.22051
|View full text |Cite
|
Sign up to set email alerts
|

FUS‐immunoreactive inclusions are a common feature in sporadic and non‐SOD1 familial amyotrophic lateral sclerosis

Abstract: Objective Amyotrophic lateral sclerosis (ALS) is a fatal disorder of motor neuron degeneration. Most cases of ALS are sporadic (SALS), but about 5-10% of ALS cases are familial (FALS). Recent studies have shown that mutations in FUS are causal in approximately 4-5% of FALS and some apparent SALS cases. The pathogenic mechanism of the mutant FUS-mediated ALS and potential roles of FUS in non-FUS ALS remain to be investigated. Methods Immunostaining was performed on postmortem spinal cords from 78 ALS cases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(191 citation statements)
references
References 33 publications
(87 reference statements)
7
181
1
2
Order By: Relevance
“…The gain-of-toxic and/or loss of normal function of FUS or TDP-43 may contribute to the pathogenesis of SALS and FALS. 5,15,16 In this study, we further found that the adenoviral vector-mediated low-grade overexpression of human FUS reduced both BTBD10 expression and the Akt phosphorylation at Ser473 (which correlates with Akt activation) (Supplementary Figure S4), whereas the adenovirusmediated low-grade overexpression of TDP-43 showed a minimal tendency to reduce BTBD10 expression in some human cultured cells (Supplementary Figure S5). The overexpression of FUS by only B1.5-2-fold more than the endogenous level is enough to reduce the BTBD10 level.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The gain-of-toxic and/or loss of normal function of FUS or TDP-43 may contribute to the pathogenesis of SALS and FALS. 5,15,16 In this study, we further found that the adenoviral vector-mediated low-grade overexpression of human FUS reduced both BTBD10 expression and the Akt phosphorylation at Ser473 (which correlates with Akt activation) (Supplementary Figure S4), whereas the adenovirusmediated low-grade overexpression of TDP-43 showed a minimal tendency to reduce BTBD10 expression in some human cultured cells (Supplementary Figure S5). The overexpression of FUS by only B1.5-2-fold more than the endogenous level is enough to reduce the BTBD10 level.…”
Section: Discussionmentioning
confidence: 59%
“…Second, recent studies have shown that transgenic overexpression of FALS-linked G85R-SOD1 causes presynaptic dysfunction and a locomotion defect in C. elegans 12 and that transgenic overexpression of TAR DNA-binding protein-43 (TDP-43) or fused in sarcoma (FUS) induces both motor neuron death and a locomotion defect in C. elegans. 13,14 As TDP-43 and FUS, both of which were RNA/DNA-binding proteins, have been recently identified as major components of cytoplasmic ubiquitinated inclusion bodies in most ALS cases, including FALS and sporadic ALS (SALS) cases, and various missense mutations of TDP-43 and FUS cause FALS in an autosomal-dominant fashion, 5,15,16 it is hypothesized that the gain-of-toxic-function and/or the loss of normal function of TDP-43 or FUS is linked to motor neuron death. These results together suggest that C. elegans can be used as an animal model of human motor neuron diseases.…”
mentioning
confidence: 99%
“…The "ALS pathway" described in the KEGG database (www.genome.jp/kegg/pathway/hsa/hsa05014. html) does not currently include recent discoveries, including key processes such as mRNA metabolism (53,54). We therefore generated an "ALS network" by creating a list of proteins found in inclusions, data from supersaturation scores, connectivity network analysis, and existing KEGG pathways (ALS, regulation of autophagy, glutamatergic synapse, RNA transport, mRNA surveillance pathway, transcription factors, ubiquitin-mediated proteolysis, and protein processing in the endoplasmic reticulum; www.genome.jp/ kegg/pathway.html), and used this list to construct a new model for functional disruption in ALS (Fig.…”
Section: Coaggregators Are More Supersaturated Than Native Interactormentioning
confidence: 99%
“…Motor neuron degeneration is associated primarily with the pathological aggregation of ubiquitin, fused in sarcoma protein, and the transactive response DNA binding protein (TAR) DNAbinding protein of 43-kDa in the cytoplasm of motor neuron cell bodies [114,115]. In addition, ALS has also been associated with an important impairment of energy metabolism [116].…”
Section: Alsmentioning
confidence: 99%